Levinas and Literature. New Directions - Fagenblat, Michael (Perspectives on Jewish Texts and Contexts, 2021)
The posthumous publication of Emmanuel Levinas's wartime diaries, postwar lectures, and drafts for two novels afford new approaches to understanding the relationship between literature, philosophy, and religion. This volume gathers an international list of experts to examine new questions raised by Levinas's deep and creative experiment in thinking literature at the intersection of philosophy and religion.